In your notebook, set up the following subtraction in a vertical format and select the correct answer.
Find 2p 2 + 3p - 4 less - 2p 2 - 3p + 4.
4p2 + 6p + 8
4p2 - 6p - 8
4p2 + 6p - 8
0

Question

Asked 1/29/2015 8:54:54 PM

Updated 1/30/2015 5:28:16 AM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [1/30/2015 5:24:59 AM]

denesfin|Points 60|

Ice chan|Points 40|

= p^2 - pq - q^2 + pq

= p^2 - q^2

jeifunk|Points 41348|

jeifunk|Points 41348|

Question

Asked 1/29/2015 8:54:54 PM

Updated 1/30/2015 5:28:16 AM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [1/30/2015 5:24:59 AM]

Rating

3

2p^2 + 3p - 4 - (- 2p^2 - 3p + 4)

= 2p^2 + 3p - 4 + 2p^2 + 3p - 4

= 4p^2 + 6p - 8

= 2p^2 + 3p - 4 + 2p^2 + 3p - 4

= 4p^2 + 6p - 8

Added 1/30/2015 5:24:52 AM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [1/30/2015 5:46:22 AM]

3

-y(2y^3 - 8)

= -y*2y^3 + y*8

= -2y^4 + 8y

= -y*2y^3 + y*8

= -2y^4 + 8y

Added 1/30/2015 5:25:23 AM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [1/30/2015 5:51:58 AM]

3

x^3(x^2 + 5x + 1)

= x^3*x^2 + x^3*5x + x^3*1

= x^5 + 5x^4 + x^3

= x^3*x^2 + x^3*5x + x^3*1

= x^5 + 5x^4 + x^3

Added 1/30/2015 5:26:24 AM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [1/30/2015 5:58:01 AM]

3

-2x^a(-4x^b - 2x^3 + 5x)

= -2x^a*(-4x^b) + 2x^a*2x^3 - 2x^a*5x

= 8x^(a+b) + 4x^(a+3) - 10x^(a+1)

= -2x^a*(-4x^b) + 2x^a*2x^3 - 2x^a*5x

= 8x^(a+b) + 4x^(a+3) - 10x^(a+1)

Added 1/30/2015 5:28:16 AM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [1/30/2015 6:05:35 AM]

29,301,609

questions answered

There are no comments.